2010
DOI: 10.1159/000321485
|View full text |Cite
|
Sign up to set email alerts
|

Water Conservation: An Emerging but Vital Issue in Hemodialysis Therapy

Abstract: Water conservation refers to reducing the usage of water and recycling of wastewater for different purposes such as irrigation, laundry and sanitation. As water scarcity increases worldwide, dialysis facilities should be focused on salvaging water. However, most of them still ignorantly discard to the sewer huge volumes of this reusable resource. This article reviews the current water conservation techniques in hemodialysis and the potential benefits drawn when using this technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…We completely support the idea of promoting awareness for this green initiative in the nephrology community (regional We read with interest the article by Tarrass et al [1] which was recently published in Blood Purification . The authors described the extent of water consumption in hemodialysis therapy and potential strategies for water saving.…”
mentioning
confidence: 65%
“…We completely support the idea of promoting awareness for this green initiative in the nephrology community (regional We read with interest the article by Tarrass et al [1] which was recently published in Blood Purification . The authors described the extent of water consumption in hemodialysis therapy and potential strategies for water saving.…”
mentioning
confidence: 65%
“…Today, the reject water is reused by a limited number of dialysis facilities in different countries for irrigation, laundry, sanitation, or for the generation of steam for sterilization …”
Section: Discussionmentioning
confidence: 99%
“…Multiple uses of reject water or dialysate effluent can be considered but are highly dependent on the constraints faced in each state. Limited groups have published their actions, notably in the United Kingdom, Australia, and Morocco …”
Section: Introductionmentioning
confidence: 99%
“…Not only should we be cognizant of predialysis RO reject water wastage, but little or no attention has been given to the potentials for the use of postdialysis effluent dialysate. Nearly a decade ago, researchers in Morocco described the use of RO membrane treatment of spent dialysate effluent to recycle it for the agricultural use . At the 2018 European Dialysis and Transplant Association (EDTA) meeting in Copenhagen, Greek researchers reported an interesting poster where used dialysate was given as a fertilizer in orange production: they reported that orange groves fertilized with dialysate effluent produced a significantly better crop than those fed with commercial fertilizer .…”
Section: Watermentioning
confidence: 99%